Rentabilidade de estratégias de momento no IBOVESPA: aplicação de critérios de risco para seleção de carteiras - Teixeira, Daniel dos Santos (2014)
This paper presents the use of Beta and Beta variation of assets belonging to the Bovespa as new criteria for the construction new srategies of winners and losers portfolios. The results show that the strategies currently on the basis of varying Betas and Beta variation of assets belonging to the Bovespa index, generate positive returns over the subsequent periods of 6 or 12 months, but it showed that these strategies, when applied in everychange of Brazil's main stock index, were less profitable than the usual strategies based on the total return on assets in the period 1995-2013.